2020
DOI: 10.3906/yer-1812-13
|View full text |Cite
|
Sign up to set email alerts
|

Upper Paleocene-lower Eocene calcareous nannofossil stratigraphy at the Misheiti Section, Central Sinai, Egypt

Abstract: Dababiya Quarry Beds (DQBs; Dupuis et al., 2003) that were documented in several sections in Egypt (Tantawy, 2006; Khozyem et al., 2013). 2. Studied section and methods Twenty-two bulk rock samples were investigated from the upper Paleocene-lower Eocene at the Misheiti Section, Central Sinai, Egypt (Figure 1). Smear slides were prepared according to Bown and Young (1998) and investigated using a Zeiss Axio-Photo microscope at Florida State University, USA. We counted 300-400 calcareous nannofossil specimens on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The Misheiti Section, Central Sinai, Egypt, according to Kasem, Wise Jr, Faris, et al (2020b) (Luciani et al, 2007). Moreover, the Tremp Formation (SBZ 3 to SBZ 6) of the Ager Basin, Central Pyrenees, Spain that contains the cyclic sequence of paralic succession with marine carbonate is correlated to the Patala Formation (SRX 1 to SRX 3) and concluded that the upper part of the Tremp Formation that contains the paralic succession held the P-E boundary (Minelli et al, 2013).…”
Section: Palaeocene-eocene Boundary Interval Within the Patala Formationmentioning
confidence: 99%
“…The Misheiti Section, Central Sinai, Egypt, according to Kasem, Wise Jr, Faris, et al (2020b) (Luciani et al, 2007). Moreover, the Tremp Formation (SBZ 3 to SBZ 6) of the Ager Basin, Central Pyrenees, Spain that contains the cyclic sequence of paralic succession with marine carbonate is correlated to the Patala Formation (SRX 1 to SRX 3) and concluded that the upper part of the Tremp Formation that contains the paralic succession held the P-E boundary (Minelli et al, 2013).…”
Section: Palaeocene-eocene Boundary Interval Within the Patala Formationmentioning
confidence: 99%